PEREMPUAN MADURA SEBAGAI SIMBOL PRESTISE DAN PELAKU TRADISI PERJODOHAN - Mardhatillah, Masyithah (Sunan Kalijaga State Islamic University & The Asia Foundation, 2014)
Maduranesse women are generally considered as prestige symbol of society, family, even a man. By this reason,Â they are treated as well as possible to keep the prestige stable even higher. However in some degree, the treatment seems not totally advantageous for women in the sense that they have limited access to make various important decisions for their lives especially in choosing the spouse. Maduranesse society still tend to choose arranged marriage for their daughters that the daughters donâ€™t have significant role in making any decision related with arranged marriage, engagement, even marriadge itself. As the prestige maintainer, Maduraness female teenagers are also supposed to be in an engagement or marriadge relationship as soon as they get the first menstruation. They all are the common tradition of Maduranesse people which is also strengthened by some local wisdom well-alive in the society. In the other hand, this common ryhtm of arranged marriadge is in fact able to create a long-lasting marriage which is good for both, especially for women.